THE INFLUENCE OF LEVERAGE, PROFITABILITY, AND LIQUIDITY ON THE DISCLOSURE OF SUSTAINABILITY REPORTS WITH COMPANY SIZE AS A MODERATING VARIABLE IN MANUFACTURING COMPANIES IN THE CONSUMER GOODS SECTOR LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) FOR THE - Septin Yarnanda; Iskandar Muda Damanik; Fahmi Natigor Nasution (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study aims to analyze the effect of financial variables such as leverage, profitability, and liquidity on sustainability report disclosure in consumer goods sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2023 period. In addition, it examines the moderating role of firm size in strengthening or weakening these relationships. A quantitative approach was used, employing panel data regression to analyze the influence of financial variables and the moderating effect of firm size on sustainability reporting. The population in this study consists of all consumer goods sector companies listed on the IDX from 2021 to 2023, totaling 93 companies. A sample of 58 companies was selected using purposive sampling based on specific criteria that met the requirements for analysis. Secondary data were obtained from financial reports and sustainability reports published during the observation period. The results indicate that leverage, profitability, and liquidity have a positive and significant effect on sustainability report disclosure. Firm size does not moderate the effects of leverage and profitability but does strengthen the influence of liquidity on sustainability disclosure, aligning with the theory that larger firms possess more resources to support sustainability reporting. Companies are advised to improve the transparency of their sustainability disclosures by leveraging available resources, particularly when profitability and liquidity levels are high. Firm size also plays an important role. More comprehensive disclosures can enhance corporate reputation and stakeholder trust, supporting long-term sustainability.